2018
DOI: 10.2147/idr.s183916
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and antimicrobial resistance of pneumococcal isolates of pediatric invasive pneumococcal disease in China

Abstract: PurposeStreptococcus pneumoniae causes serious infections globally, including invasive pneumococcal disease (IPD). We analyze clinical features of pediatric IPD cases identified in China and antibiotic susceptibility of isolated pneumococcal strains.MethodsConfirmed pediatric IPD patients were prospectively recruited to the study. Symptoms at the time of hospitalization, laboratory tests, antimicrobial susceptibility of pneumococcal isolates, treatments, hospital stay, and residual findings at discharge were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 33 publications
8
20
4
Order By: Relevance
“…In this study, we identified a total of 287 pediatric patients diagnosed with pneumococcal pneumonia from January to December 2018 in Shanghai, China. Most of them (261,90.9%) were under 5 years old and diagnosed less in the summer, which was in line with the recent results from China (Cai et al, 2018). A male sexual superiority was also noticed among the study population, so as in other studies (Cai et al, 2018; Arushothy et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we identified a total of 287 pediatric patients diagnosed with pneumococcal pneumonia from January to December 2018 in Shanghai, China. Most of them (261,90.9%) were under 5 years old and diagnosed less in the summer, which was in line with the recent results from China (Cai et al, 2018). A male sexual superiority was also noticed among the study population, so as in other studies (Cai et al, 2018; Arushothy et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Most of them (261,90.9%) were under 5 years old and diagnosed less in the summer, which was in line with the recent results from China (Cai et al, 2018). A male sexual superiority was also noticed among the study population, so as in other studies (Cai et al, 2018; Arushothy et al, 2019). In current study, chronic diseases were observed in 15.7% patients, which is an independent risk factor for pneumonia-related mortality in children (Zhang et al, 2013; Sonego et al, 2015; Nguyen et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…In the Asian Network for Surveillance of Resistant Pathogens (ANSORP) report [49], following the revised CLSI breakpoints, the prevalence of penicillin resistance for nonmmeningitis strains was 0.7% and for meningitis isolates was 57.7%. In the included twelve articles [17,[24][25][26][27][28][29][30][31][32][33][34], only four separately reported penicillin resistance rates of meningitis and nonmmeningitis isolates [17,[24][25][26] and the data were consistent with the results from ANSORP [49]. Actually, it is important for researchers and clinical workers to distinguish specimen types and resistance patterns for meningitis and nonmmeningitis isolates.…”
Section: Discussionmentioning
confidence: 99%
“…We screened 42 articles in our preliminary search, of which 16 studies [17,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] fulfilled inclusion criteria and were included in the final analysis ( Fig. 1).…”
Section: Data Reviewmentioning
confidence: 99%
See 1 more Smart Citation